Reading use in preschool (Research, Society and Development, 2016)
Reading in preschool is a time of awakening the taste and pleasure in reading, it is also a source of reflection, discovery and learn to listen. It is then necessary that the contact with the reading start from pre-school, with a variety of texts and the teacher also has the habit of reading in their daily lives. Therefore, this study aimed to investigate the benefits of daily reading in the classroom pre-school life of a student, which the characteristics of a player and teacher reading to children's identity formation. The methodology used was a literature search followed by an analysis performed through reading, data comparison and author’s speech. Through bibliographical analysis we realized the importance of the teacher's role in encouraging the development of a practice of reading that becomes present in the school environment in order to promote that the habit and enjoy reading in children, the conclusion was that the reading is the main influence in personal training and academic, contributing to a variety of factors for the construction of the identity of the student.